Local caspase activity directs engulfment of dendrites during pruning. - Williams, D.W.; Kondo, S.; Krzyzanowska, A.; Hiromi, Y.; Truman, J.W. (Nature Neuroscience, 2006)
Pruning is important for sculpting neural circuits, as it removes excessive or inaccurate projections. Here we show that the removal of sensory neuron dendrites during pruning in Drosophila melanogaster is directed by local caspase activity. Suppressing caspase activity prevented dendrite removal, whereas a global activation of caspases within a neuron caused cell death. A new genetically encoded caspase probe revealed that caspase activity is confined to the degenerating dendrites of pruning neurons.